Analisis Spasial Pengaruh Faktor Sosial dan Lingkungan terhadap Prevalensi Hipertensi - Zen, Rizqi Annisa; Pramana, Setia (Seminar Nasional Official Statistics, 2024)
Hypertension is one of the most common cardiovascular diseases suffered by people in the world. In Indonesia, around 34.1 percent of the population aged 18 years and over suffers from hypertension. Factors that cause hypertension are always associated with genetic and lifestyle factors, even though environmental and social factors also contribute to the occurrence of hypertension. This research was conducted to identify the influence of social and environmental factors on hypertension. The data used comes from Basic Health Research (Riskesdas) in 2018, publications by the Central Statistics Agency (BPS), as well as satellite image data. Satellite imagery is able to provide an accurate and up to date picture of air quality, surface temperature and vegetation distribution. The research was carried out with a spatial approach using the Spatial Autoregressive Model (SAR) method. The results of the analysis show that the lag parameter has a significant effect on the prevalence of hypertension. Meanwhile, the only variable that has a significant influence is Land Surface Temperature (LST), while the variables are GRDP per capita, RLS, TPT, Nitrogen Dioxide (NO2), Carbon Monoxide (CO), Sulfur Dioxide (SO2), and Normalized Difference Vegetation Index (NDVI) has no significant effect on the prevalence of hypertension.